Strategies for thermal management in lithium-ion batteries: Mitigating thermal runaway risk - Mallimoggala, Srinivas; Devi, K Rama (Vietnam Journal of Science and Technology, 2026)
Thermal runaway in lithium-ion batteries (LIBs) is currently one of the major safety concerns in high-energy applications that include electric vehicles, aerospace, and others. Thermal management especially must be well done to avert disastrous failures. This paper evaluates the use of aluminum as a heat spreader in controlling thermal runaway in a lithium-ion battery system with a 7s4p configuration using COMSOL Multiphysics. The thermal analysis of different cooling techniques is done in this work, examining air cooling and phase change material as well as the aluminum heat spreader concerning the peak temperature, heat removal, and thermal reliability. The analysis carried out on the results has shown that the use of aluminum heat spreaders greatly reduces the temperatures that reach their peak and improves heat spreading - facts that advocate for their effectiveness in increasing the thermal safety of lithium-ion battery packs.